Incidence And Mortality From Bladder Cancer In The Republic Of Uzbekistan - Tillashaykhov M.N; Boyko E. V; Janklich S.M; Tuychiyev A.P; Tillashaykhova R.M (Zien Journals, 2024)
Analysis of main statistical indicators of bladder cancer in the Republic of Uzbekistan in 2020.
Keywords: stages; oncological; Uzbekistan